Self-Compassion and Psycho-Physiological Recovery From Recalled Sport Failure - Ceccarelli, Laura A.; Giuliano, Ryan J.; Glazebrook, Cheryl M.; Strachan, Shaelyn M. (Frontiers in Psychology, 2019)
Failure inherent to high-performance sport can precipitate emotional distress that can impair athletes’ performance and physical and mental health. Identifying factors that allow athletes to manage failure to sustain their health is critical. Self-compassion, treating oneself kindly in response to failure, may help athletes manage failure; it buffers against negative affective psychological responses, yet athletes often fear self-compassion. It is unknown whether the benefits of self-compassion extend to athletes’ physiological responses to failure and whether fear of self-compassion has an influence on psychological and physiological responses to failure, beyond self-compassion. The purpose of this study was to examine the influence of self-compassion on athletes’ psychological and physiological responses when recalling a sport failure and determine if fear of self-compassion exerted unique effects, beyond self-compassion. Participants (n=91; M age=21) were university or national-level athletes. In this laboratory-based, observational study, athletes were connected to a multi-modal biofeedback system to measure physiological responding at baseline, during a stress induction (imagining a past performance failure), and during a recovery period. Physiological responding was assessed according to athletes’ high-frequency heart rate variability (HRV), indexing parasympathetic nervous system activity, during the stress induction and recovery phase. Next, to assess psychological reactivity, athletes completed a series of scales (behavioral reactions, thoughts, and emotions). Regression analyses revealed that self-compassion predicted athletes’ HRV reactivity to the stress induction (β = .30, p < .05). There was no relationship between self-compassion and HRV recovery. Further, self-compassion predicted adaptive behavioral reactions (β = .46, p < .01), and negatively predicted maladaptive thoughts (β = -.34, p < .01) and negative affect (β = -.39, p < .01). Fear of self-compassion explained additional variance in some maladaptive thoughts and behavioral reactions. Results suggest that self-compassion promotes adaptive physiological and psychological responses in athletes relative to a recalled sport failure and may have implications for performance enhancement, recovery and health outcomes. Further, addressing athletes’ fears of self-compassion may also be important in promoting optimal psychological recovery.